Tentative study on radial endobronchial ultrasonography evaluating airway wall thickness before and after bronchial thermoplasty. (2022) - Yan, Shang; Haidong, Huang; Chengjie, Zhu; Qin, Wang; Hohenforst-Schmidt, Wolfgang; Freitag, Lutz; Tsakiridis, Kosmas; Zarogoulidis, Paul; Arnaoutoglou, Christos; Ioannidis, Aris; Chong, Bai
Abstract: Aim: We aimed to observe the clinical practicing value of radial endobronchial ultrasonography evaluating airway wall thickness before and after bronchial thermoplasty. Methods: We selected two patients who received bronchial thermoplasty in our hospital. We measured the thickness of each segmental airway wall of each patient by radial endobronchial ultrasonography, and observed the difference before and after the therapy. All the treatments and measurement were performed by a designated bronchoscopist and the locations and depths of the ultrasound probe were relatively fixed, to reduce the operational error. Results: In both two patients, the mean thicknesses of all segmental airway walls was 4.9 ± 0.7 mm before the first session of BT; the mean thickness was 4.13 ± 0.92 mm before the second session; the mean thickness was 2.69 ± 0.68 mm before the third session; the mean thickness was 2.7 ± 0.5 mm in the follow-up measurement at six months after the BT treatment; all thicknesses of airway wall were significantly reduced comparing with those before treatment; all the thicknesses of the airway walls were stable without any tendency of thickening after six months. Although the airways in the right middle lobe of both two patients were not received BT, their thicknesses were also decreased comparing with those before the treatment; both upper lobes bronchus of both two patients were not activated in the first and second sessions, but their thicknesses were also decreased at the third measurement. Conclusion: Radial endobronchial ultrasonography is a simple and practical method to measure the thickness of patient's airway wall. Bronchial thermoplasty can effectively reduce the thickness of airway wall. It can reduce airway smooth muscle by direct activation and other possible more complicated mechanism, which need further research.